Static and Dynamic Magnetic Properties of Fe3o4 Nanotubes - Escrig-Murua, J; Saavedra-Díaz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In this paper, our objective was to investigate the static and dynamic magnetic properties of Fe3O4 nanotubes that are 1000 nm long, by varying the external radius and the thickness of the tube wall. We performed a detailed numerical analysis by simulating hysteresis curves with an external magnetic field applied parallel to the axis of the tubes (along the z-axis). Our findings indicate that nanotubes with an external radius of 30 nm exhibit non-monotonic behavior in their coercivity due to a change in the magnetization reversal mechanism, which was not observed in nanotubes with external radii of 80 nm. Additionally, we explored the dynamic susceptibility of these nanotubes and found that the position and number of resonance peaks can be controlled by manipulating the nanotube geometry. Overall, our study provides valuable insights into the behavior of Fe3O4 nanotubes, which can aid in the design and improvement in pseudo-one-dimensional technological devices. © 2023 by the authors.